Estimating the effects of nuclear power facilities on local income levels: A quasi-experimental approach - Michihito Ando (Uppsala University, Department of Economics, 2013)
This paper studies how the establishment of Nuclear Power Facilities (NPF) in the 1970s and 1980s has affected local per capita income levels in NPF-located municipalities in Japan by using the synthetic control method (SCM). Eight quantitative case studies using the SCM clarify that the effects of NPF establishment on per capita taxable income levels are highly heterogeneous, but often economically meaningful and in some cases huge: an 11 % increase on average, a 62 % increase in Rokkasho village in 2002 and a 30 % increase in Tomioka town in 2002. On the other hand, a few NPF-located municipalities receive weak or negligible effects from NPF establishment. I also examine the statistical significance of individual treatment effects with several placebo tests and find that the treatment effects of 4 out of the 8 NPF locations are larger than 95% of placebo effects.
urn:nbn:se:uu:diva-194094
Keywords: H71; O18; R53; 330; local economic growth; nuclear power facilities; synthetic control method